Immune Activation Following Vaccination of Streptococcus iniae Bacterin in Asian Seabass (Lates calcarifer, Bloch 1790) - Tanpichai P. (2023)
Juvenile Asian seabass (Lates calcarifer) (body weight 10 ± 0.7 g) were intraperitoneally injected with 1012 CFU fish−1 of formalin-killed Streptococcus iniae. The protective efficacy of the vaccine on survival and infection rate was assessed upon challenge at 4, 8, 12, 20, and 28 weeks post-vaccination. The results revealed that the challenged vaccinated fish showed no mortality at all time points, and the control fish presented 10–43.33% mortality. The infection rate at 2 weeks post-challenge was 0–13.33% in the vaccinated fish and 30–82.35% in the control group. At 8 weeks post-vaccination, the vaccinated fish showed comparable ELISA antibody levels with the control; however, the antibody levels of the vaccinated fish increased significantly after the challenge (p < 0.05), suggesting the presence of an adaptive response. Innate immune genes, including MHC I, MHC II, IL-1β, IL-4/13B, and IL-10, were significantly upregulated at 12 h post-challenge in the vaccinated fish but not in the control. In summary, vaccination with S. iniae bacterin provided substantial protection by stimulating the innate and specific immune responses of Asian seabass against S. iniae infection.